Effect of Technical Competencies of Women in Core Mining Activities on Team Operational Performance in South Africa - Munilal, Suneshnee (My University, 2023)
The objective of this study was to establish the relationship between the technicalcompetencies of women in the core mining activities and team operationalperformance in the South African mining industry.A gold-mining company in South Africa was selected for this study and 15 interviewparticipants were chosen based on their discipline being a core mining activity.Thematic analysis was used to analyse the collected data and the common themeswere concluded.The findings of this study highlighted that the issue of inclusion of women in the coremining activities is not a matter of the technical competencies of women, but ratherthe lack of exposure of women in the technical environment, which disadvantageswomen from having the technical competencies required for team operationalperformance. Women have the technical competencies to thrive in the mining industryand the technical competencies of women are comparable to those of their malecounterparts.The lack of inclusion of women in the mining industry is also due to prehistoricmisconceptions of women in a technical environment, and this social exclusion ofwomen can be resolved by leaders in the mining industry making a deliberate effort togive recognition to women who are keen to succeed in the harsh mining industry.Women who have the technical competencies in the core mining activities should beselected for technical roles based on their identified technical competencies.The technical competencies required to thrive in any core mining activity are problem-solving skills, decision-making skills, delegation of tasks, listening and communicationand knowledge of risk and safety management, planning, task scheduling, peoplemanagement, and team collaboration and cohesion.It was found from this study that women are more risk averse than men and women-led teams in the mining industry have been found to have improved safety statistics
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: echnical Competencies; Women in Core Mining Activities; Team Operational Performance; SDG-8: Decent work and economic growth